Analysis data spatial for nutrition programs: a review using geographic information system - Utomo, Bedjo; Triwiyanto, Triwiyanto; Luthfiyah, Sari; Setyobudi, Sugeng Iwan (International Journal of Public Health Science (IJPHS), 2024)
Nutritional problems are public health problems that are still found in developing countries, one of the prevention efforts requires nutritional data information. Geographic information systems (GIS) is an information system application that can analyze spatial data, such as population distribution, regional boundaries, and access to health centers. This study aims to examine the use of spatial data analysis with GIS in monitoring nutrition programs. The methods used in data retrieval use scientific database searches such as PubMed, Scopus, and Google Scholar as well as VOSviewer application with Keywords such as "spatial data analysis", "Geographic Information System", "Nutrition program", and design and implementation. The results of this study state that the GiS has a broad impact on the dissemination of nutritional status information, especially in areas with nutritional vulnerability, GIS spatial analysis can help understand the factors that contribute to malnutrition, as well as environmental factors that influence the success of nutrition programs. The results of the study concluded that priority areas of nutrition program intervention on the use of Geographic Information Systems can be used to make decisions and analyze spatial data to reduce the burden of disease in these areas. Furthermore, this review further enhances the understanding of the use of GiS for nutrition program interventions in improving the success of nutrition programs.